2011
DOI: 10.1037/a0022295
|View full text |Cite
|
Sign up to set email alerts
|

Professional burnout in clinical military psychologists: Recommendations before, during, and after deployment.

Abstract: Clinical military psychologists (CMPs) hold one of the most difficult positions within professional psychology. Given their exposure to a variety of environmental, physical, psychosocial, and emotional stressors, professional burnout (PB) can be a serious issue for CMPs. In order to (a) protect job satisfaction, (b) increase professional confidence, (c) facilitate a long and rewarding military career, and (d) ensure competent care is provided to our clients, a two-pronged approach of CMPs taking care of themse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…The inherent concerns faced by psychologists include complex client presentations, hard‐won clinical outcomes, time‐consuming and highly intense work conditions, profuse administration responsibilities, and challenging client–therapist boundaries (Baker, ). There is a growing body of literature concerning the effects of job‐related stress and professional burnout among psychologists (Ackerley, Burnell, Holder, & Kurdek, ; Barnett & Hillard, ; Bearse, McMinn, Seegobin, & Free, ; Cushway & Tyler, ; Linnerooth et al., ). Studies have shown up to 44.1% of surveyed American psychologists, across multiple agencies, fell within the high burnout (emotional exhaustion) range (Rupert & Morgan, ).…”
Section: Burnout Among Psychologists In Trainingmentioning
confidence: 99%
“…The inherent concerns faced by psychologists include complex client presentations, hard‐won clinical outcomes, time‐consuming and highly intense work conditions, profuse administration responsibilities, and challenging client–therapist boundaries (Baker, ). There is a growing body of literature concerning the effects of job‐related stress and professional burnout among psychologists (Ackerley, Burnell, Holder, & Kurdek, ; Barnett & Hillard, ; Bearse, McMinn, Seegobin, & Free, ; Cushway & Tyler, ; Linnerooth et al., ). Studies have shown up to 44.1% of surveyed American psychologists, across multiple agencies, fell within the high burnout (emotional exhaustion) range (Rupert & Morgan, ).…”
Section: Burnout Among Psychologists In Trainingmentioning
confidence: 99%
“…Burnout may also be differentiated from similar constructs, compassion fatigue and vicarious traumatization (Baird, & Jenkins, ; Beaumont, Durkin, Hollins Martin, & Carson, ; Deighton, Gurris, & Traue, ). Unlike the client‐contingent, and sometimes short‐lived experiences of compassion fatigue or vicarious traumatization, burnout has been defined as a condition which evolves from a combination of both stressful external (occupational) and internal (personal) factors, and can lead to long‐lasting implications (Linnerooth, Mrdjenovich, & Moore, ; Morse, Salyers, Rollins, Monroe‐DeVita, & Pfahler, ). Contrarily, burnout and occupational stress are both defined by work‐related psychological injury at least partly due to undue pressures and work demands, and thus may present similar constructs (Health and Safety Executive, n.d.).…”
Section: Introductionmentioning
confidence: 99%
“…It is common in jobs with a high degree of social interaction or demands, and in the helping professions (Maslach et al, 2001) such as social work, teaching, and healthcare. Job burnout has been shown to have a negative impact on occupational indicators, such as job performance, job satisfaction, absenteeism, and staff turnover (Linnerooth and Mrdjenovich, 2011). Furthermore, burnout symptoms have been linked to a variety of mental and physical health problems such as depression, insomnia, and gastrointestinal disturbances (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%